Lecturer’ Knowledge and Self-efficacy to Employ Digital Technologies for Curriculum Instruction in Tertiary Institutions in North-east, Nigeria - OGUNDARE, Samuel Akinola; ANIMASAHUN, Veronica Oluwatoyin; ABIDOYE, James Alabi (Ilorin Journal of Education, 2023)
The study assessed the lecturers’ knowledge and self-efficacy to employ digital technologies for curriculum delivery in tertiary institutions in North East, Nigeria. The study employed survey research type with population of numerical strength of one hundred and fifty-three lecturers teaching basic science and technology in all universities and colleges of education in North East, Nigeria. Ninety colleges of education and university lecturers were sampled for the study. The participants responded to a 26- item structured validated by peer experts questionnaire with reliability index of 0.81 on the level of lecturers’ knowledge, self-efficacy, utilization and challenges in digital technologies for curriculum instruction. Data collected were analysed with the use of frequency counts, simple percentages and mean. The lecturers consider themselves not very competent especially in terms of content knowledge, TPACK-ISTE self-efficacy and frequent usage of digital technologies for teaching and learning of basic science and technology. Besides, the challenges hindering the usage of digital technologies by lecturers for instruction in teaching and learning processes were indicated. Lecturer should undergo training and retraining through seminars, workshops, among others to enhance positive change for both the teacher and student’s level in the usage of technologies for teaching-learning process.